Оцінка стану ендотеліальної функції судин у хворих на гіпотиреоз - Zubkova, S.T.; Bulat, O.V.; Mykhailenko, O.Yu. (Ендокринологія | Endokrynologia, 2011)
Оцінка стану ендотеліальної функції судин у хворих на гіпотиреоз